STRUKTUR KOMUNITAS MAKROZOOBENTOS DI DANAU PONDOKLAPAN DESA NAMAN JAHE KECAMATAN SALAPIAN KABUPATEN LANGKAT (Community Structure of Macrozoobenthos in Pondok Lapan Lake’s Desa Naman Jahe Kecamatan Salapian Kabupaten Langkat) - Desy Ariska; Yunasfi Djayus; Ahmad Muhtadi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Makrozoobenthos can be used as bioindicators as it can determine the condition of a bodywater. This study focused on community structure of macrozoobenthos and measurement ofphysical and chemical factors. This study was conducted in January until March 2015.Macrozoobenthos retrived done using Eckman grabb, samples sorted using the Hand sorting.Samples were obtained identified in the Integrated Laboratory of USU. The highest density ofspecies found in Bithynia tentaculata were namely 48 ind / m2 was found in station I and thelowest in Campeloma decisum species were namely 6 ind / m2 was found at stations II andIV. The value of the highest diversity (H ') contained in the station III were namely 1.09 andthe lowest at station IV were namely 1.04. Habitat Similarity between stations based onphysical parameters that are most similar water chemistry contained in the station I and IIIwere namely 94%. Habitat Similarity between species are most similar to the station I and IIIwere namely 92%. Based on a Pondok Lapan lake’s LQI value categorized into pollutedwaters being were namely 3 and based on the FBI Pondok Lapan Lake’s category rather poorwaters that have were namely 6.Keywords : Pondok Lapan Lake’s, Community Structure, Macrozoobenthos